Cushing’s Syndrome during Pregnancy: Post Delivery Adrenalectomy Consequent to Medical Management without Adrenal Enzyme Inhibitors: - Esfahanian, Fatemeh; Faiz, Firoozeh; Zamani, Mohammad Mahdi; Hantoushzadeh, Sedigheh (Galen Medical Journal, 2012)
A 32-year-old female, gravid two, para one, with Cushing’s syndrome (CS) was admitted to our hospital at 25 week of gestation with severe hypercortisolism. Basal urinary free cortisol (UFC) was elevated about 10 times above the upper limit of normal in two separate times and plasma cortisol failed to suppress after an overnight 1mg dexamethasone suppression test but Adrenocorticotropic hormone (ACTH) level was suppressed. An abdominal non-contrast magnetic resonance imaging (MRI) disclosed a 3-cm right adrenal mass (Fig. 1). Due to her critical general condition, the adrenalectomy was not performed. At 30 week of gestation, by the diagnosis of severe preeclampsia she underwent an emergent cesarean section. Two weeks later, right adrenalectomy was performed via laparotomy. Pathologic examination of the gland showed a benign adrenocortical adenoma. The newborn was a healthy male who weighed 1850 gram. There was no clinical or biochemical suppression of adrenocortical function in child and they were discharged after 40 days.[GMJ. 2012;1(1):38-41]